The Community Nurse Practitioner Role to Promote the Care of Tuberculosis Patients at Home, with an Emphasis on Family - Centered Care - จิตดอน, จุฬาวรรณ (Journal of Health Sciences and Wellness, 2018)
Tuberculosis of the lung should not be incurable. It can be cured If the patient receives proper treatment and practices self-care. In the Thai population there are also cases with unsuccessful treatment. Most of the time the reason behind this is the lack of proper treatment due to the side effects of the medication given to patients with pulmonary tuberculosis. These side effects may range from mild to severe or even life threatening. As a result, the patients are getting discouraged and tired of the treatment, eventually discontinue. In this situation family focused nursing care is essential. Families should take part of the treatment. Closely related family members who love and understand each other could give the right support to the patient, and act if the condition of the sick family member gets worse. Nurses practicing community service are close to both the families and the health care providers, therefore they play a crucial role when the patient returns home from an institution and continues home based treatment. Another important role of the community nurse is to supporting families in making decisions about how to care for the patient in the family. Their tasks include providing information, comprehensive treatment, prevention, and rehabilitation options to individuals, families, and communities. This article is aimed to present nursing care concepts of community care of pulmonary tuberculosis patients focusing on the nurse as a role model in promoting successful treatment even if at times there is a resistance from the patients and their families, in order to achieve better quality of life.